048 Assessment of CPR performance by 13 to 14-year-old schoolchildren after a single 2 h training session. (22nd September 2015) - Greer, N; McCormick, C; McCluskey, D
Abstract : Introduction: The most cost effective way of increasing the number of people capable of giving CPR is to train children in school. The optimal age at which children should receive this instruction remains in doubt as do the factors which affect the ability of children to deliver effective life support. Aims: To assess performance of CPR by 13 to 14-year-old children after a single 2 h training session delivered in school. Methods: One month after training, 122 school children were asked to perform CPR for 3 min using a skills reporter manikin. They were randomised to use either 15:2 or 30:2 ratio. Chest compression depths were recorded onto a laptop computer and analysed to determine if the ratio used or the gender or body mass index (BMI) of the child influenced their ability to give CPR. Results: Children of 13 to 14 years are capable of giving effective CPR after a single 2 h training session delivered in school. When using the 15:2 ratio, boys give significantly more chest compressions of ≥38 mm than girls. Girls of this age give significantly more effective chest compressions when using the 15:2 rather than the 30:2 ratio. Gender Number %≥38 mm SD Male 22 30.5 37.3 Female 57 12.8 25.4 p=0.009 Ratio Number %≥38 mm SD 15:2 57 12.8 25.4 30:2 43 4.6 13.8 p=0.02 The BMI of 13 to 14-year-old girls has a highly significant influence on her ability to give chest compressions of ≥38 mm. Conclusions Children of 13 years or more can learn to give effective CPR after a single 2 h training session delivered in their school. The ability of children of this age to give effective chest compressions is influenced by their gender, their body mass index and the ratio of chest compressions to ventilations used. These factors should be taken into consideration when training programmes are being developed for use in schools.